A Feasibility Study on the Establishment of Genial Food Park in Kymco Motors 971 Aurora Boulevard, Cubao, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Genial Food Park offers service and product. Service because the business will rent food stalls inside the food park at the same time will put own stall inside the food park to offer them a product like mildly alcoholic drinks, juice and shakes. For own stall the business will offer them variety of street foods only. The food park who wants to rent a stall for the vacant space of the location, if is highly suggested for them to offer all kinds of variety of foods. The researcher used survey questioners to determine the viability of the business and identify. The factors and potential problems that could occur in developing the business idea. 100 respondents composed of students, professionals, and residents to utilized Financial Statement. The business is situated along Kymco Motors 971 Aurora Boulevard, Cubao, Quezon City. Based on the financial statement the researchers found out that the business is highly acceptable and feasible with 26% (ROI) Returned of Investment of the first year and will increase the operation of the business. The business is indeed profitable and acceptable to the market and spent time with friends and family to relax in Food Park that why the researchers came up with this business and to implement the operation of Genial Food Park business.
Keywords: feasibility, establishment, genial food park